Teachers' classroom management self-efficacy, perceived classroom management and teaching contexts from beginning until mid-career. (October 2020) - Lazarides, Rebecca; Watt, Helen M.G.; Richardson, Paul W.
Abstract: Teacher self-efficacy for classroom management is an important component of teachers' identity with implications for their teaching quality. Theoretically, it has been described that contextual variables play an important role for self-efficacy development and its consequences. However, little is known about the interrelationships of job resources and demands with teacher self-efficacy, and consequences for teachers' professional behaviors. We extend teacher self-efficacy research by drawing on the Job Demands-Resources model in examining contextual influences on developmental dynamics between classroom management self-efficacy and teacher-reported classroom management, from prior to qualifying as a teacher until mid-career. Participants were 395 primary and secondary Australian school teachers. Longitudinal structural equation models showed teachers' classroom management self-efficacy positively related to aspects of their perceived classroom management, particularly during early career. Between early and mid-career, the positive relationship between self-efficacy and classroom management was moderated by early career excessive demands. Implications are outlined for teacher education and school administration. Highlights: Longitudinal relationships of teachers' self-efficacy and classroom management. Contextual resources and demands were examined as predictors and moderators. Teachers' self-efficacy supported their development of perceived classroom structure. Excessive demands during early career were highly detrimental. Theoretical contributions to the self-efficacy and Job Demands-Resources literatures.